Charge transfer in sapphyrin-fullerene hybrids employing dendritic ensembles - Grimm, Bruno; Karnas, Elizabeth; Brettreich, Michael; Ohta, Kiminori; Hirsch, Andreas; Guldi, Dirk Michael; Torres, Tomas; Sessler, Jonathan L. (Journal of Physical Chemistry B, 2010)
A new approach to creating noncovalent charge transfer ensembles is described. It is based on two components that are linked through anion-receptor interactions. The first component is sapphyrin, a pentapyrrolic expanded porphyrin, which is capable of carboxylate anion recognition and more importantly can act as a photodonor when irradiated in the presence of a suitable electron acceptor. The second component is the electron acceptor and consists of one of two different C fullerene cores functionalized with multiple carboxylate anion groups arranged in a dendritic fashion. Depending on the specific choice of the fullerene carboxylate anion dendrimer employed in ensemble construction, 1:1 or 1:2 complexes are formed when the C cores are titrated with sapphyrin. The resulting noncovalent arrays undergo sapphyrin-to-fullerene electron transfer when irradiated with 387 nm light. This gives rise to charge separated states with lifetimes of ca. 470 and 600 ps in the case of the 1:1 and 1:2 sapphyrin-fullerene ensembles, respectively. © 2010 American Chemical Society.